2022
DOI: 10.3390/cryst12070954
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and Electrochemical Characterization of Laser-Cladded Ti-Nb-Ta Alloy for Biomedical Applications

Abstract: Titanium (Ti) and its alloys are predominant choices for use as biomaterials in human implants. Research has shown the adverse effects of using commercial Ti alloy Ti-6Al-4V in the human body, and this presents a need for viable alternatives. In this study, Ti alloy Ti-17Nb-6Ta was manufactured by laser cladding—a prominent additive manufacturing (AM) technology. Laser cladded specimens were evaluated for their in vitro and electrochemical behavior. A human osteosarcoma cell line (MG-63 cells) was used for in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
(34 reference statements)
2
3
0
Order By: Relevance
“…The microscopic investigations of the TiNbTa-ATZ fracture surfaces revealed that the strength of the hybrid material is determined by adhesive failure along the interface between glass solder and TiNbTa alloy as well as cohesive fracture of the glass solder, which is in line with previous observations [18,20,24]. Within TiNbTa alloys, oxide films, e.g., TiO2, Nb2O5, and Ta2O are formed [29,30], and the reaction of the chemical compounds in the surface layers with the glass solder is crucial in the formation of the material bond [17,18]. Hey et al [48] described the formation of Ti5Si3 due to the reaction of SiO2 with Ti using a comparable silica-based glass solder.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The microscopic investigations of the TiNbTa-ATZ fracture surfaces revealed that the strength of the hybrid material is determined by adhesive failure along the interface between glass solder and TiNbTa alloy as well as cohesive fracture of the glass solder, which is in line with previous observations [18,20,24]. Within TiNbTa alloys, oxide films, e.g., TiO2, Nb2O5, and Ta2O are formed [29,30], and the reaction of the chemical compounds in the surface layers with the glass solder is crucial in the formation of the material bond [17,18]. Hey et al [48] described the formation of Ti5Si3 due to the reaction of SiO2 with Ti using a comparable silica-based glass solder.…”
Section: Discussionsupporting
confidence: 88%
“…Using medical β-titanium (β-Ti) alloys in glass-soldered hybrid materials is a promising approach, since β-Ti alloys possess increased elasticity compared to pure α (cp-Ti) or α+β (Ti-6Al-4V) Ti alloys [25]. They are mostly composed of biocompatible elements such as Nb, Ta, and Zr [26][27][28], which are highly corrosion resistant [29,30] and additionally promote osteogenesis [31]. Furthermore, β-Ti alloys can be additively manufactured by laser powder bed fusion (PBF-LB/M) [32], allowing advanced processability, e.g., direct fabrication of complex structures, such as open porous scaffolds or specifically functionalized implant surfaces [26,33].…”
Section: Introductionmentioning
confidence: 99%
“…The microscopic investigations of the fracture surfaces (Figure 6) revealed that the strength of the hybrid material is determined by the adhesive failure along the interface between the glass solder and Ti-based material, as well as by the cohesive fracture of the glass solder, which is in line with previous observations [21,25,67]. Within the TiNbTa alloys, oxide films (e.g., TiO 2 , Nb 2 O 5 , and Ta 2 O), are formed [74,75], and the reaction of the chemical compounds in the surface layers with the glass solder is crucial in the formation of the material bond [20,21]. Hey et al [76] described the formation of Ti 5 Si 3 due to the reaction of SiO 2 with Ti using a comparable silica-based glass solder.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast to Co-28Cr-6Mo, the glass solder and ATZ ceramics are highly biocompatible [26]. In addition, it has been shown that osteoblasts cultured on TiNbTa exhibit a gene differentiation indicating bone formation [47], and Ti/Nb/Ta alloys are highly corrosion-resistant [74,75]. Furthermore, contrary to Ti-6Al-4V, where potentially harmful aluminum and vanadium ions are released [9][10][11]34], niobium and tantalum are highly biocompatible with no cytotoxic effects have been described so far [83].…”
Section: Discussionmentioning
confidence: 99%
“…Niobium and tantalum are particularly promising alloying elements. They stabilize the β-phase in Ti base alloys, form highly corrosion-resistant passive oxide layers, and are biocompatible [13,16,17,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%